Finite element analysis of lumbosacral soft tissue at sitting posture at desktop computer (Annals of Medical Research, 2023)
Aim: This study aims to numerically determine the biomechanical effect of von Mises stress, induced at different flexion angles of the spine while sitting at a desktop computer, on the soft tissues in the front and back of the lumbosacral region, as well as to contribute to determining the ideal sitting posture.Materials and Methods: Three-dimensional (3D) soft tissue models were created using Solidworks. Static structural analyses of the tissues were performed in ANSYS with the finite element method (FEM). Stress distribution and stress values occurring in the anterior and posterior sides of the lumbosacral region at 0, 15, 30, and 45 spine flexion angles were analyzed separately. The values of von Mises stress formed in the anterior and posterior soft tissues of the lumbosacral region gradually increased with the increase in the flexion angle. Furthermore, the stress values in the anterior and posterior soft tissues were compared with each other for the same spinal flexion angle.Results: The von Mises stress values were found to be higher in the posterior side only at 0 degrees, whereas at 15, 30, and 45 degrees, they were higher in the anterior side. As a result, the most suitable position for sitting at a computer was determined. Lower flexion angles of the spine, such as 0 and 15 degrees, create less stress on the anterior and posterior sides of the lumbosacral region.Conclusion: Sitting postures with a flexion angle of the spine higher than 0-15 degrees are not appropriate, and desktop users are not recommended to adopt such a posture. The results of the analysis could be used to better understand the effects of prolonged sitting on the lumbosacral area and to design interventions to reduce the risk of injury or discomfort.